2007
DOI: 10.1021/jm061389p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nonpeptide CCR5 Receptor Agonists by Structure-based Virtual Screening

Abstract: A three-dimensional model of the chemokine receptor CCR5 has been built to fulfill structural peculiarities of its alpha-helix bundle and to distinguish known CCR5 antagonists from randomly chosen drug-like decoys. In silico screening of a library of 1.6 million commercially available compounds against the CCR5 model by sequential filters (drug-likeness, 2-D pharmacophore, 3-D docking, scaffold clustering) yielded a hit list of 59 compounds, out of which 10 exhibited a detectable binding affinity to the CCR5 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 54 publications
10
117
0
Order By: Relevance
“…Similarly, using molecular databases spiked with known binders, a number of studies based on combinations of different scoring functions (such as Gold [68], Dock [69], CScore (Tripos), Fresno [70], Score [71], FlexX [72], and PMF [66]) have demonstrated the applicability of molecular docking at GPCR models to virtual screening [9,10,73]. In agreement with the expectations set by these studies, a variety of docking programs and scoring functions have been successfully applied to the discovery of novel ligands for a plethora of GPCRs, including neurorokinin [74,75], adrenergic [76], chemokine [75,77], dopamine [75], serotonin [75,78], cannabinoid [79], and free fatty acid receptors [80], among others.…”
Section: Structure-based Methodologiesmentioning
confidence: 72%
“…Similarly, using molecular databases spiked with known binders, a number of studies based on combinations of different scoring functions (such as Gold [68], Dock [69], CScore (Tripos), Fresno [70], Score [71], FlexX [72], and PMF [66]) have demonstrated the applicability of molecular docking at GPCR models to virtual screening [9,10,73]. In agreement with the expectations set by these studies, a variety of docking programs and scoring functions have been successfully applied to the discovery of novel ligands for a plethora of GPCRs, including neurorokinin [74,75], adrenergic [76], chemokine [75,77], dopamine [75], serotonin [75,78], cannabinoid [79], and free fatty acid receptors [80], among others.…”
Section: Structure-based Methodologiesmentioning
confidence: 72%
“…The virtual screening strategy was performed using this model and by focusing on the specificity interaction patch between the BDNF N-terminal region and the TrkB-d5 domain ( Figure 1). The Bioinfo-DB database of 1.6 million commercially available drug-like compounds (30) was first filtered for lead-like properties (31), including notably predicted water solubility and blood-brain barrier permeation, to afford 78,045 compounds. Preliminary docking studies of the BDNF terminal epitope (H 1 SDPAR 6 ) with various docking algorithms indicated that the FlexX program (32) was particularly well suited for docking in the TrkB specificity site.…”
Section: Modeling Of the Bdnf/trkb Specificity Patch And Docking-basementioning
confidence: 99%
“…The structural coordinates of human PrP C (HuPrP C ) (1QLZ, Protein Data Bank) were used for molecular modeling studies of the PrP and the search for a putative binding site conserved in both PrP C and PrP Sc isoforms. The in silico screening was performed using the Bioinfo chemical library (Kellenberger et al, 2007) and the Gold 2.0 Software (Jones and Thornton, 1997;Verdonk et al, 2003). Candidate molecules were visualized at the conserved binding site using the Insight II Accelrys software with the Silicon Graphics SGI 02 R10000 workstation.…”
Section: Ethics Statement the Comité Régional D'ethique De Montpellimentioning
confidence: 99%